Assessment of the Cardiovascular Risk Profile of Infants Exposed to Pre-eclampsia in-utero: A Prospective Case-Control Study in South African Children of African Ancestry - Nkeh-Chungag, Benedicta Ngwenchi; Engwa, Godwill Azeh; Businge, Charles; Kutllovci-Hasani, Kaltrina; Kengne, Andre P.; Goswami, Nandu (Frontiers in Cardiovascular Medicine, 2021)
Background: It has been reported that maternal gestational environment may be programmed to have a significant impact on foetal and offspring health later in life. Studies have shown that children born of pre-eclamptic mothers are prone to obesity, hypertension and diabetes in their adult life. However, such findings are yet to be established in an African population. This protocol is for a study aiming to investigate the relationship between pre-eclampsia (PE) and cardiovascular risk in children born to pre-eclamptic mothers in a South African population. Methods: A prospective cohort design will be employed to recruit pre-eclamptic and normotensive pregnant women and their offspring after birth. Pregnant women will be assessed for cardiovascular risk factors including pre-eclampsia, obesity, haemodynamics, lipid and glycaemic indices, oxidative stress and vascular function at 30 weeks of gestation. The cardiovascular risk profile of their offspring will be assessed at birth and six weeks later. The difference in cardiovascular risk profile between children born to the pre-eclamptic and normotensive mothers and the correlation between maternal and offspring cardiovascular risks will be investigated. Discussion: This will be the first prospective study to assess the in-utero effect of cardiovascular risk on offspring born to pre-eclamptic women of African ancestry. It is expected that findings from this study will provide information on the cardiovascular effect of in-utero exposure to PE in a population of African ancestry. This knowledge will advise policy on the management of women with pre-eclampsia with a view of protecting cardiovascular health in offspring.